YASHIL IQTISODIYOT VA RAQAMLI MOLIYALASHTIRISHDA EKOLOGIK STARTAPLAR HAMDA ULARNING RIVOJLANISHI - Jo‘rayev Umidjon Shuxratjon o‘g‘li; Usmonova Muslimaxon (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article analyzes the impact of green economy and digital financing on the development of ecological startups in Uzbekistan. It examines government support, investments from international financial institutions, and existing challenges. Additionally, it provides the necessary conditions and recommendations for the successful growth of ecological startups.